Properties and microstructure of pre-formed foamed concretes - Hilal, Ameer Abdulrahman (2015)
In construction buildings, use of thermal insulating materials is essential and beneficial not only by reducing the cooling/heating cost and the structural element sizes but also reducing the pollution of the environment which results from heavy use of fuel.